Work status and work ability after radical prostatectomy or active surveillance for prostate cancer. (3rd May 2020) - Nilsson, Rasmus; Dahl, Alv A.; Bernklev, Tomm; Kersten, Hege; Haug, Erik S.
Abstract: Objective: Being able to work is important for health-related quality of life (HRQoL), and little is known about work life after radical treatment for prostate cancer (PCa). The aim was to investigate work status (WS) and work ability (WA) after radical prostatectomy (RP) or active surveillance (AS) for PCa, and to identify factors associated with reduced WA. Materials and methods: This is a retrospective cross-sectional study of 606 men treated with RP ( n  = 442) or AS ( n  = 164) at two Norwegian general hospitals. In 2017, they were asked to complete questionnaires measuring adverse effects (AE), HRQoL, aspects of work life and psychological factors at a median of 4.1 (range 1.3–8.1) years after diagnosis. Clinical data were retrieved from medical records. WS was categorized into employed, unemployed or retired. WA was rated using the Work Ability Index. Regression analyses were performed to find factors associated with reduced WA. Results: WS was similar for the RP and AS groups at diagnosis and survey. There was a small reduction in WA from diagnosis to survey and the difference between the RP and AS groups was non-significant. Older age, poorer self-rated health, poorer incontinence score, more chronic fatigue, and increased anxiety and depressive symptoms were associated with reduced WA, while treatment method, urinary bother and use of pads were not. Conclusion: The impact of RP and AS on WS and WA was almost similar. Age and psychological variables were more strongly associated with reduced WA than cancer-related variables.